1985
DOI: 10.1152/ajpgi.1985.249.4.g457
|View full text |Cite
|
Sign up to set email alerts
|

Hypersensitive prostaglandin and thromboxane response to hormones in rabbit colitis

Abstract: Inflammation of the colon is associated with increased production of prostaglandins (PG) and thromboxanes (Tx), and these eicosanoids may contribute to the inflammatory, secretory, and motility dysfunctions in colitis. To evaluate the potential role of peptide hormones in the enhanced eicosanoid release, colitis was established in rabbits by a delayed-type hypersensitivity reaction to dinitrochlorobenzene and by an immune-complex-mediated reaction. PG and Tx were identified in the venous effluent of isolated p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…For example, Zipser et al [16] found approximate threefold increases in TxB 2 , using both dinitrochlorobenzene and also indomethacin to induce inflammation. Using rabbits instilled rectally with trinitrobenzenesulfonic acid (TNBS), studies have reported even greater increases in TxB 2 (10-fold) [17].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Zipser et al [16] found approximate threefold increases in TxB 2 , using both dinitrochlorobenzene and also indomethacin to induce inflammation. Using rabbits instilled rectally with trinitrobenzenesulfonic acid (TNBS), studies have reported even greater increases in TxB 2 (10-fold) [17].…”
Section: Discussionmentioning
confidence: 99%
“…A slowly metabolizable analogue of prostaglandin E2 (16,16-dimethyl prostaglandin E2) has recently been shown to accelerate mucin secretion from N2 cells [9]. Many of the previously reported responses of the intestinal mucosa to kinins are mediated indirectly by generation of cyclooxygenase metabolites of arachidonic acid [1,[17][18][19][20][21][22]. It should be noted, however, that kinin-induced prostaglandin synthesis is thought to occur primarily in the subepithelial elements [20,21] that would not be present in the goblet cell monolayer model.…”
Section: Discussionmentioning
confidence: 99%
“…However in intestine, kinins may be more important as pathophysiological mediators. It has been shown that bradykinin produces 2 -4 -fold greater concentration of prostanoids in animals with experimental colitis than in normal controls, which may contribute to the increased intestinal secretion of chloride (Zipser et al 1985). Bradykinin -induced chloride secretion by the guinea pig ileum occurs by direct binding of the ligand to its receptor (Maning et al, 1982).…”
Section: Kinins and Kinin Receptors In Ibdmentioning
confidence: 99%